2014
DOI: 10.5194/bg-11-1727-2014
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and metabolic profiling reveal strong influence of water table and land-use patterns on classification of degraded tropical peatlands

Abstract: Abstract. Tropical peatlands from southeast Asia are undergoing extensive drainage, deforestation and degradation for agriculture and human settlement purposes. This is resulting in biomass loss and subsidence of peat from its oxidation. Molecular profiling approaches were used to understand the relative influences of different land-use patterns, hydrological and physicochemical parameters on the state of degraded tropical peatlands. As microbial communities play a critical role in biogeochemical cascades in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 90 publications
2
14
0
Order By: Relevance
“…Environmental conditions strongly impact the structure of microbial communities (Bahram et al, 2018). The effects of water table and total nitrogen content on bacterial communities in SP samples (Table 3) matches well with previous studies in different types of peatlands (Mishra et al, 2014;Urbanová and Bárta, 2016;Zhong et al, 2017). Interestingly we further found that RT and CART also responded to water table and total nitrogen content.…”
Section: Environmental Factors Shaping Bacterial Communitiessupporting
confidence: 86%
“…Environmental conditions strongly impact the structure of microbial communities (Bahram et al, 2018). The effects of water table and total nitrogen content on bacterial communities in SP samples (Table 3) matches well with previous studies in different types of peatlands (Mishra et al, 2014;Urbanová and Bárta, 2016;Zhong et al, 2017). Interestingly we further found that RT and CART also responded to water table and total nitrogen content.…”
Section: Environmental Factors Shaping Bacterial Communitiessupporting
confidence: 86%
“…Anthropogenic disturbances, in particular settlements and logging (secondary forest), led to higher diversity indices (Fig .6). On the contrary, sites surrounded by oil palm plantations displayed the lowest diversity indices, supporting results by Mishra et al (2014) who found similar results in peatlands. Furthermore, the OTU overlapping of major anthropogenic activities (i.e settlements and oil palm plantations) in Supp.…”
Section: Possible Pathogenic Bacteria And/or Anthropogenic Influence supporting
confidence: 84%
“…2005; Kolmakova et al, 2014;Lemke et al, 2009;Newton et al, 2011;Read et al, 2015;Staley et al, 2013). While there are studies related to the freshwater-marine gradients of rivers such as studies by Crump and Hobbie (2005) and Fortunato et al (2013)and tropical peatlands (Kanokratana et al, 2011;Mishra et al, 2014;Yule et al, 2016;Too et al, 2018), to the author's knowledge, this is the first study which links both freshwater-marine gradients as well as tropical peatlands as a cohesive component (i.e tropical peat-draining river to coastal ecosystem). Due to the high diversity and fast generation time, the first responders to environmental changes (both natural and anthropogenic events such as storms, upwelling and pollutants) are microbial communities (Hunt and Ward, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…This was particularly apparent in Sebungan, where the canopy was closed and temperatures were lower. Sebungan had a lower mean WTD than the RSPO recommendations at the time of measurement and thus fresh peat may have been exposed to heterotrophic bacteria, increasing the rate of R h from Sebungan (Lim et al, 2012;Mishra et al, 2014;Carlson et al, 2015).…”
Section: Mitigation Optionsmentioning
confidence: 99%
“…Modifying peatlands for agricultural management can alter the biogeochemistry and trace gas fluxes from these systems due to the introduction of artificial drainage ditches that lower the water table and create an aerated zone for root growth, raising the soil redox potential (Hirano et al, 2012;Mishra et al, 2014;Tonks et al, 2017). In these more oxic conditions, methanogenesis is inhibited and aerobic degradation pathways predominate, namely peat oxidation from heterotrophic respiration (R h ; Hooijer et al, 2012;Miettinen et al, 2017;Warren et al, 2017).…”
Section: Introductionmentioning
confidence: 99%